The role of media and educational guidance in students’ enrollment in the field of physical education and sports - zahoui, nacer (sports creativity, 2025)
Information and guidance are among the most essential services and educational processes that have occupied many educators, professionals, and thinkers in the field. This is due to their significant impact on the future of students, firstly, and their surrounding environment, secondly. These processes work to achieve a kind of balance and harmony between the aspirations and ambitions of the individual and the requirements of society. Any disruption in these processes results in a waste of educational resources and moral and material losses for both the individual and society.